Human Merkel cell polyomavirus infection I. MCV T antigen expression in Merkel cell carcinoma, lymphoid tissues and lymphoid tumors. - Shuda, Masahiro; Arora, Reety; Kwun, Hyun Jin; Feng, Huichen; Sarid, Ronit; Fernández-Figueras, María-Teresa; Tolstov, Yanis; Gjoerup, Ole; Mansukhani, Mahesh M; Swerdlow, Steven H; Chaudhary, Preet M; Kirkwood, John M; et al. (International journal of cancer. Journal international du cancer, 2009)
Merkel cell polyomavirus (MCV) is a recently discovered human virus closely related to African green monkey lymphotropic polyomavirus. MCV DNA is integrated in approximately 80% of Merkel cell carcinomas (MCC), a neuroendocrine skin cancer linked to lymphoid malignancies such as chronic lymphocytic leukemia (CLL). To assess MCV infection and its association with human diseases, we developed a monoclonal antibody that specifically recognizes endogenous and transfected MCV large T (LT) antigen. We show expression of MCV LT protein localized to nuclei of tumor cells from MCC having PCR quantified MCV genome at an average of 5.2 (range 0.8-14.3) T antigen DNA copies per cell. Expression of this putative viral oncoprotein in tumor cells provides the mechanistic underpinning supporting the notion that MCV causes a subset of MCC. In contrast, although 2.2% of 325 hematolymphoid malignancies surveyed also showed evidence for MCV infection by DNA PCR, none were positive at high viral copy numbers, and none of 173 lymphoid malignancies examined on tissue microarrays expressed MCV LT protein in tumor cells. As with some of the other human polyomaviruses, lymphocytes may serve as a tissue reservoir for MCV infection, but hematolymphoid malignancies associated with MCC are unlikely to be caused by MCV.
Keywords: Amino Acid Sequence; Antigens, Polyomavirus Transforming; Carcinoma, Merkel Cell; DNA, Viral; Fluorescent Antibody Technique; Gene Dosage; Gene Expression Regulation, Viral; Humans; Immunoblotting; Immunoenzyme Techniques; Lymphoid Tissue; Lymphoma; Molecular Sequence Data; Polymerase Chain Reaction; Polyomavirus; Polyomavirus Infections; Sequence Homology, Amino Acid; Skin Neoplasms; Tumor Virus Infections